Quantitative assessment of arginine methylation in free versus protein-incorporated amino acids in vitro and in vivo using protein hydrolysis and high-performance liquid chromatography. (March 2006) - Bulau, Patrick; Zakrzewicz, Dariusz; Kitowska, Kamila; Wardega, Birgit; Kreuder, Joachim; Eickelberg, Oliver
Arginine methylation constitutes a posttranslational modification dependent on the action of protein arginine methyltransferases (PRMTs). Using S-adenosylmethionine as a methyl donor, PRMTs catalyze the formation of monomethylarginine (L-NMMA), asymmetric dimethylarginine (ADMA), or symmetric dimethyl arginine (SDMA). Protein arginine methylation is involved in the regulation of signal transduction, RNA export, and cell proliferation, but a quantitative view of arginine methylation of the cell and tissue proteome remains to be performed. In this study, we developed a high-performance liquid chromatography (HPLC)-based method to accurately quantify methylated arginines in free and protein-incorporated amino acid pools of cell and tissue extracts, using protein precipitation and hydrolysis, HPLC separation, and fluorescence detection for the simultaneous quantification of L-arginine (L-Arg), L-NMMA, ADMA, and SDMA. This method permits accurate assessment of the degree of protein arginine methylation in complex biological samples. Using this method, we determined dynamic changes in protein methylation in vitro in cells subjected to proteasome inhibition. We furthermore demonstrate differential methylation patterns in heart and kidney lysates in vivo. Thus, the described method will greatly facilitate our understanding of the role of arginine methylation in physiology and pathophysiology and of the effects of pharmacological interventions on arginine methylation in select cell culture models.